Surgical Peritonitis or Not: An Analysis - Hernández, José Luis García; Cabello, José de Jesús Urbina; Alva, María De Los Ángeles Carmona; Ríos, Aldebharán Avila; Suárez, Ivonne Alondra León; Barrón, Gema Méndez; Segura, Carlos Andrés Salas; Sanciprián, Rafael Martínez; Elizondo, Camila Rivera; Sánchez, Morelos Adolfo García (British Journal of Healthcare and Medical Research, 2025)
Introduction: To analyze the impact of peritoneum in the surgical area, it is necessary to go back to the anatomy, physiology, histology and even embryology of peritoneum. Since this structure becomes the "pivot"! strategic to perform or not the surgical act. Objective: To describe the experience of patients who presented surgical peritonitis in the Surgery departments. Method: A retrospective, longitudinal, observational and descriptive study of the Surgery Service was conducted in two public health hospitals. Results: A total of 211 records of patients with surgical peritonitis were reviewed, of which 123 were men (58.29%), 88 women (41.71%), with an average age of 57 years, ranging from 19 to 81 years. Intestinal perforation secondary to multiple pathologies is the leading cause of surgical peritonitis, accounting for 37%. The surgeries were initially urgent with an is of 198 patients, which is 93.83%, and the rest was scheduled or priority surgery. Adjusted morbidity 26.54%. Discussion: Abdominal peritonitis is classified into primary and secondary; some authors have mentioned tertiary peritonitis, where patients with complicated intra-abdominal infections have been diagnosed with the most severe and severe form. Regarding the quality of secondary peritonitis, where the therapeutic protagonist is surgery and with exhaustive washing of the abdominal cavity, acute abdomen. Conclusions: acute peritonitis in most patients is the tacit expression of a consequence of a surgical pathology, where the clinical scenario is florid or evident, leading to overtreatment in the so-called primary peritonitis. However, there are cases that, even though they are primary peritonitis, benefit exponentially from the surgical event, when draining and performing an exhaustive surgical wash.